2014
DOI: 10.1007/s00438-014-0834-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of novel wheat NBS domain-containing sequences and their utilization, in silico, for genome-scale R-gene mining

Abstract: In crop improvement, the isolation, cloning and transfer of disease resistance genes (R-genes) is an ultimate goal usually starting from tentative R-gene analogs (RGAs) that are identified on the basis of their structure. For bread wheat, recent advances in genome sequencing are supporting the efforts of wheat geneticists worldwide. Among wheat R-genes, nucleotide-binding site (NBS)-encoding ones represent a major class. In this study, we have used a polymerase chain reaction-based approach to amplify and clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
3
0
2
Order By: Relevance
“…Using degenerate primers to isolate resistance gene analogs from different plant species has so far been an effective strategy (Yaish et al, 2004;Palomino et al, 2006;Bouktila et al, 2014). In the present study, we identified and characterized 10 RGAs in three pea varieties, using four primer combinations designated from G. max (Kanazin et al, 1996) and S. tuberosum (Leister et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Using degenerate primers to isolate resistance gene analogs from different plant species has so far been an effective strategy (Yaish et al, 2004;Palomino et al, 2006;Bouktila et al, 2014). In the present study, we identified and characterized 10 RGAs in three pea varieties, using four primer combinations designated from G. max (Kanazin et al, 1996) and S. tuberosum (Leister et al, 1996).…”
Section: Discussionmentioning
confidence: 98%
“…Using this approach, several RGAs have been isolated from various species, including wheat (Zhang et al, 2011;Bouktila et al, 2014), A. thaliana (Meyers et al, 2003), faba bean and chickpea (Palomino et al, 2006), soybean (Graham et al, 2000), pea (Timmerman-Vaughan et al, 2000), and Medicago truncatula (Zhu et al, 2002). The identified RGAs correspond to different disease specificities, and, in some cases, their mapping has provided evidence that they co-segregate with resistance markers related to disease (Meyers et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…This type of experimentation represents a low cost alternative for studies on biological functions with very precise computational models when compared with laboratory conditions. Computational analyzes have been used in the characterization of several proteins and enzymes in both eukaryotes and prokaryotes, in search of genes linked to parasitism and resistance in host species [25][26][27][28][29][30][31] . The identification of proteins involved in the relationship of parasitism of nematodes and plants can provide important tools for research that develop plant species with resistant genes and in the search for mechanisms that avoid the breakdown of this resistance by phytonematodes.…”
Section: Introductionmentioning
confidence: 99%
“…La mayor parte de los genes R clonados pertenecen a la familia NBS-LRR. Esta familia tiene unos motivos muy conservados en su secuencia, lo que ha permitido el diseño de cebadores degenerados basados en los motivos conservados de genes R conocidos para aislar secuencias análogas a genes de resistencia o RGAs (Resistance Gene Analogs) en otras especies vegetales mediante técnicas que utilizan la reacción en cadena de la polimerasa (PCR) (Bouktila et al, 2014;Deng et al, 2000;Donald et al, 2002;Graham et al, 2000;Meyers et al, 2003;Palomino et al, 2006;Timmerman-Vaughan et al, 2000;Wan et al, 2010;Xu et al, 2005;Zhang et al, 2011;Zhu et al, 2002), ya sea con ADN total y utilizando geles de agarosa (Djebbi et al, 2015;Kanazin et al, 1996;Leister et al, 1996;Reddy et al, 2015;Wan et al, 2012;Yaish et al, 2004;Yu et al, 1996) o geles de poliacrilamida (Chen et al, 1998) para la separación de los fragmentos, o utilizando ADNc en la técnica llamada "NBS profiling" que combina la digestión del ADN con enzimas de restricción con una posterior amplificación por PCR (Brugmans et al,2008;Sanz et al, 2013;van der Linden et al, 2004).…”
Section: Genes Runclassified
“…La mayor parte de los genes R clonados en plantas pertenecen a la familia NBS-LRR. Esta familia tiene unos motivos muy conservados en su secuencia, lo que ha permitido el diseño de cebadores degenerados basados en dichos motivos para aislar secuencias análogas a genes de resistencia o RGAs (Resistance Gene Analogs) en un gran número de especies vegetales (Bouktila et al, 2014;Djebbi et al, 2015;Graham et al, 2000;Kanazin et al, 1996;Leister et al, 1996;Meyers et al, 2003;Palomino et al, 2006;Timmerman-Vaughan et al, 2000;Wan et al, 2012;Yaish et al, 2004;Yu et al, 1996;Zhang et al, 2011;Zhu et al, 2002) Meyers et al (1999) y Lukasik y Takken (2009) describieron una serie de motivos conservados que caracterizan las secuencias de estos como TIR o TNL (siglas del dominio Toll interleukin receptor) y No-TIR o CNL.…”
Section: Motivos Conservadosunclassified